PENGARUH STRESSOR, KEPUASAN KERJA, KOMPENSASI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI PT EKASARANA IDOLAMU - Devraj Silaban; Deni Wardani (Ibs Press, 2025)
This study aims to analyze the effect of stressors, job satisfaction, compensation, and work culture on employee performance at PT Ekasarana Idolamu. The research is motivated by the phenomenon of declining employee performance caused by excessive work pressure, dissatisfaction with compensation, and the inconsistent implementation of work culture within the company. The research employs a quantitative approach using a sample of 38 employees selected through a saturated sampling technique. The data were analyzed using the Partial Least Squares- Structural Equation Modeling (PLS-SEM) method with the SmartPLS version 4 application. The results reveal that stressors have a negative effect on employee performance, indicating that higher levels of work pressure lead to lower performance. Job satisfaction has a positive effect and is identified as the most dominant factor in improving employee performance. Compensation has a positive effect but provides a relatively smaller contribution to performance improvement. Meanwhile, work culture positively influences employee performance, demonstrating that the values of discipline, openness, and teamwork are able to strengthen employees’ performance and engagement.